IMPROVING TECHNOLOGY FOR DISINFECTING GRAIN FROM PESTS OF BREAD STOCK USING ULTRA-HIGH RADIATION FREQUENCIES - Тuychiyeva, D.М. (PT. Antis International Publisher, 2024)
This study examines the potential of microwave electromagnetic fields (EMF) for pest control in grain storage facilities. Traditional methods of grain disinsection often require halting production and using harmful chemicals, which can affect grain quality and the environment. By contrast, EMF technology allows for continuous, chemical-free pest control, preserving grain quality and reducing environmental impact. The research investigates optimal EMF settings, focusing on power level and exposure time to maximize pest elimination without compromising grain characteristics. Results indicate that, at 180 W/m² for 120–160 seconds, microwave treatment effectively eradicates pests, enhances germination rates, and maintains grain physicochemical properties. Additionally, microwave-treated flour displays increased water absorption, which improves bread texture and quality. These findings suggest that EMF technology not only serves as an efficient pest management solution but also improves product quality, offering a sustainable alternative to conventional methods and aligning with food industry trends in safety and sustainability. This study thus provides valuable insights into integrating innovative, eco-friendly techniques in grain processing.